(untitled) (Torani Journal of Fisheries and Marine Science, 2026)
Traditional smoked fish enterprises are an important economic activity supporting the livelihoods of coastal communities. However, the perishable nature of fishery products causes the supply chain to face various challenges, including uncertainty in raw material supply, limited coordination, and distribution risks. This study aimed to analyze the Food Supply Chain Network (FSCN) of traditional smoked fish enterprises in Bone Regency, Indonesia, by examining the supply chain structure, supply chain management, business processes, resources, product, information, and financial flows, as well as identifying key bottlenecks and supply chain risks. This study employed a qualitative method using the FSCN approach and was conducted from November 10, 2023, to January 12, 2024. Data were obtained through observations, interviews with 38 smoked fish producers selected using a census method as the primary respondents, and in-depth interviews with 20 other supply chain actors selected purposively as supporting informants. Data were analyzed descriptively using the FSCN framework, covering supply chain structure, supply chain management, business processes, resources, product, information, and financial flows, as well as the identification of key bottlenecks and supply chain risks. The results showed that the smoked fish supply chain network in Bone Regency consisted of five main actors: fishers, raw material suppliers, smoked fish producers, traders/retailers, and final consumers, supported by secondary members providing production inputs. Producers served as central actors that created added value through the processing of fresh fish into smoked fish products. Product flow moved from fishers and suppliers to producers and was subsequently distributed through traders/retailers to final consumers. Information flow was bidirectional, whereas financial flow moved from downstream to upstream, with transactions predominantly conducted on a cash and trust-based basis. Business processes included raw material procurement, production, replenishment, and customer order fulfillment. FSCN analysis identified raw material supply as the main key bottleneck due to dependence on fishers’ catches, which are influenced by seasonal and weather conditions, compounded by limited processing technology and the risk of quality deterioration during distribution. These findings indicate that strengthening raw material supply continuity, improving coordination among supply chain actors, and enhancing institutional integration are key strategies for improving the resilience and sustainability of the traditional smoked fish supply chain in Bone Regency.